PERAN WANITA JAWA DALAM SERAT WULANG ESTRI DI ERA REVOLUSI INDUSTRI 4.0 - Sri Mulyani; NFN Mulyana (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2022)
The role of Javanese women as a companion and responsible for the survival of family life. Serat Wulang Estri was one of the works of Javanese literature which contains the advices or teachings of a father to his daughter. This contains about the attitude of women who have been married to husbands who should be taught to Javanese women since they were teenagers. The concept of Javanese women in general society tends to see women as human beings who have roles behind or called